2018
DOI: 10.1038/nature26136
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin resistance in cavefish as an adaptation to a nutrient-limited environment

Abstract: Periodic food shortages are a major challenge faced by organisms in natural habitats. Cave-dwelling animals must withstand long periods of nutrient deprivation, as—in the absence of photosynthesis—caves depend on external energy sources such as seasonal floods1. Here we show that cave-adapted populations of the Mexican tetra, Astyanax mexicanus, have dysregulated blood glucose homeostasis and are insulin-resistant compared to river-adapted populations. We found that multiple cave populations carry a mutation i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 214 publications
(214 citation statements)
references
References 34 publications
9
202
3
Order By: Relevance
“…Moreover, they found that the transgenic homologous zebrafish has a reduction in scale size. This has been reported in other zebrafish type 1 diabetes models as well (Carnovali et al, ; Riddle et al, ). Neither of these studies have specifically looked into the rest of the skeletal structures.…”
Section: A Mexicanus As a Model To Identify Adult Skeletal Disorderssupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, they found that the transgenic homologous zebrafish has a reduction in scale size. This has been reported in other zebrafish type 1 diabetes models as well (Carnovali et al, ; Riddle et al, ). Neither of these studies have specifically looked into the rest of the skeletal structures.…”
Section: A Mexicanus As a Model To Identify Adult Skeletal Disorderssupporting
confidence: 75%
“…Diabetes is another common metabolic disorder among humans, which is generally associated with increased risk for bone fracture; however, the pathophysiological mechanisms of diabetes‐induced bone pathologies are poorly understood, and whether diabetes increases skeletal fragility remains to be identified (Shanbhogue et al, ). Riddle et al () investigated metabolic homeostasis with regards to blood glucose regulation and found that the CF populations have dysregulated blood glucose levels and are insulin resistant. Moreover, they found that the transgenic homologous zebrafish has a reduction in scale size.…”
Section: A Mexicanus As a Model To Identify Adult Skeletal Disordersmentioning
confidence: 99%
“…If CLTCL1 started accumulating mutations during the evolution of any of these 12 species, there would have been no selective pressure to retain it, given their dietary habits. The cave fish, which lacks CLTCL1, is a notable example here because these animals have the capacity to respond to insulin but have independently evolved mutations in their insulin receptor, rendering them naturally insulin resistant, consistent with this pathway being a target for natural selection driven by diet (37). However, CHC22 can be tolerated in species that do not need it, as evidenced by CHC22-transgenic mice (4), which are viable but exhibit excessive GLUT4 sequestration and age-related high blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…94 In a recent study, we found certain cavefish populations to be insulin resistant compared with their surface ancestors due to a mutation in their insulin receptor. 103 We showed that in these populations the insulin resistance phenotype is genetically linked to an overall increase in body weight. These results made us argue that this phenotype further contributes to the fish's strategy to survive scarce times by acquiring high enough fat levels.…”
Section: Cavefishmentioning
confidence: 91%